Flask Weather Wizadry: Create a Robust App with Advanced Features and User-friendly, Mastering the Art of Forecasting - Kannammal, K.E.; V, Arcchana (Journal of Neonatal Surgery, 2025)
This study suggests the creation of a weather forecasting app based on Flask, a Python web application framework, with the addition of IBM Watson API for precise meteorological information. The project aims to create an easy-to-use platform that integrates several web development technologies, such as SQLAlchemy for database management and Flask-Login for secure authentication and authorizing. Front-end functionalities, developed using Bootstrap, JavaScript, and AJAX, include responsive design and dynamic content. Our strategy involves strict validation, safe user input handling, and strong integration with weather data sources using IBM Watson API to provide data accuracy and application reliability. Thorough testing and debugging procedures also guarantee the user experience via greater reliability. Findings indicate that applying Flask in conjunction with IBM Watson API presents a reliable solution for real-time weather forecasting, which is accurate and scalable. The current work introduces to the literature a systematic process that can be adopted by developers to create interactive and secure web applications with Flask and third-party APIs, and provides useful guidelines to new as well as experienced web developers.